Thrombocytopenia in Young Patient due to Anti Tuberculosis Drugs : A Case Report - Aryani Prawita Sari; Winariani Koesoemaprodjo (Faculty of Medicine Universitas Airlangga, 2020)
Background: Most anti-tuberculosis (ATD) drugs are relatively safe, but unusual serious reactions can occur. Thrombocytopenia is an uncommon but potentially life-threatening complication of certain ATDs and is characterized by rapid destruction of platelets whenever an offending drug is taken by a susceptible person. Rifampicin is the most common cause of thrombocytopenia.Case: A 25 years old woman came with chief complaints, shortness of breath since 1 week before admission and cough with phlegm since 2 months before admission. The patient received antibiotic and ATD. In the course of improving on sepsis and pneumonia, the patient had thrombocytopenia accompanied by melena on day 4 of treatment.Discussion: Thrombocytopenia is defined as a disorder, which showed an abnormality on the low amount of thrombocyte. Thrombocytopenia was commonly cofounded when Complete blood count (CBC) was performed. The majority of the mechanism associated with thrombocytopenia is the immune. Drug-induced Thrombocytopenia (DITP) is an exclusion diagnosis, which is obtained by ruling out other underlying causes that resulted in thrombocytopenia.Conclusion: This case illustrates that the discovery of isolated thrombocytopenia in a patient taking several medications presents a challenging clinical problem. Laboratory confirmation of drug-induced thrombocytopenia at the time of initial presentation is not possible because tests for drug-dependent anti-platelet antibodies are not available in most clinical laboratories. The diagnosis of drug-induced thrombocytopenia can be supported only by resolution of thrombocytopenia after discontinuation of therapy with the suspected drug.